2015
DOI: 10.1007/s13239-015-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

Particle Image Velocimetry Used to Qualitatively Validate Computational Fluid Dynamic Simulations in an Oxygenator: A Proof of Concept

Abstract: Computational fluid dynamics (CFD) is used to simulate blood flow inside the fiber bundles of oxygenators. The results are interpreted in terms of flow distribution, e.g., stagnation and shunt areas. However, experimental measurements that provide such information on the local flow between the fibers are missing. A transparent model of an oxygenator was built to perform particle image velocimetry (PIV), to perform the experimental validation. The similitude theory was used to adjust the size of the PIV model t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…As reported previously adhesion of polystyrene seeding particles on the PMMA fiber dummies can be observed. However, the adhesion proceeds slowly over time and becomes a restricting factor in terms of image quality for measurements over several days.…”
Section: Limitationssupporting
confidence: 86%
See 1 more Smart Citation
“…As reported previously adhesion of polystyrene seeding particles on the PMMA fiber dummies can be observed. However, the adhesion proceeds slowly over time and becomes a restricting factor in terms of image quality for measurements over several days.…”
Section: Limitationssupporting
confidence: 86%
“…Scaling up the PIV‐model was essential to increase the spatial resolution of the recorded images. We utilized similitude theory to extract three parameters from the dimension analysis : Π1=Re=ρtrueu¯dhη Π2=Hdh Π3=Δpρtrueu¯2 where Re is the Reynolds number, ρ is the density of the fluid, u¯ is the average velocity, d h is the hydraulic diameter of the flow cross section, η is the dynamic viscosity, H is the geometrical height of the fiber bundle, and Δ p is the pressure drop between in‐ and outlet.…”
Section: Methodsmentioning
confidence: 99%
“…The results of gas transfer seemed to be similar but not equal with pulsatile and constant blood flow; one reason for this effect can be the actual behavior of blood cells in oxygenators. Even with a constant blood flow, the blood cells swirl around the fibers and do not move directly from inlet to outlet , so that all blood cells get in contact with the gas exchange surface and are oxygenated completely. The pulsatile flow provokes the mixing of blood everywhere, but in oxygenators this effect already exists, so only a small improvement of gas exchange is possible and a pulsatile flow does not increase gas exchange.…”
Section: Discussionmentioning
confidence: 99%
“…In capillaries with a diameter <300 µm a blood cell free plasma layer can be observed in wall proximity . Even though fiber gaps in the fiber bundle of artificial lungs are in the same range, the flow conditions are different: PIV studies in transparent full scale artificial lungs showed fluid acceleration and deceleration . Further studies are required to determine whether this effect can be transferred to the membrane fiber bundle of artificial lungs.…”
Section: Discussionmentioning
confidence: 99%